Analysis of Human Voice Spectrum based on Regional Accent in Vowels and Consonants - Puspa Indah Devitasari; Benazir Amalia Firdausy; Shobhi Al-Ghifari Azhary; Heru Kuswanto (International Journal of Engineering, Science and Information Technology, 2021)
This study aims to analyze the spectrum of the human voice based on the accents of several regions. This research is included in the type of experimental research. Data were collected from 4 male respondents aged 23 years as research subjects. Respondents come from Central Java, East Java, Jambi, and South Sulawesi or come from Javanese, Malay, and Bugis ethnicities. Each respondent pronounces the vowels /a/ and /e/ as well as the consonants /b/, /d/, and /g/ once in each sound under normal circumstances or does not have throat problems or other things that make the sound abnormal. Voice recording is done in a closed and quiet room without any disturbance by using a microphone connected to a laptop using the cool record edit pro application. The sound spectrum was analyzed using Praat verse 2 software, then the recording was converted to *wav format. Furthermore, the sound spectrum analysis procedure uses software to determine the shape of the spectrum, the maximum or minimum pitch frequency (F0), and the formant frequency of F1-F4 in each sample. The results showed that the response of men from South Sulawesi had the highest tone of 156 Hz in the letter /b/ and 145 Hz in the letters /d/ and /g/ respectively. while the lowest tone of voice owned by men from the Jambi area is 105 Hz, 109 Hz, and 102 Hz for each consonant and the output from F0 (pitch) to F1-F4 (formant) can change and does not describe the high pitch, meaning the formant will always high.